2011
DOI: 10.1021/jp2010698
|View full text |Cite
|
Sign up to set email alerts
|

Carbonaceous Nanoparticle Molecular Inception from Radical Addition and van der Waals Coagulation of Polycyclic Aromatic Hydrocarbon-Based Systems. A Theoretical Study

Abstract: ARTICLEresults obtained with the modest 3-21G(d) basis set can be sufficiently reliable.' ASSOCIATED CONTENT b S Supporting Information. Tables reporting deformation energies, ΔS(T), and ΔH(T) values, the geometries and energetics of all optimized structures, and all vibrational frequencies. This material is available free of charge via the Internet at http:// pubs.acs.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 108 publications
(165 reference statements)
0
18
0
Order By: Relevance
“…This would require a full kinetic mechanism considering both the formation and fragmentation routes for both pathways. Both the aromatic and aliphatically bonded complexes have been shown to form bonds of sufficient energy to withstand flame temperatures, ,, however, both will be subject to radical-induced fragmentation to varying degrees. Examples of this are hydrogen abstraction from aliphatics leading to β-scission that leads to the rapid fragmentation of aliphatic fuels as well as hydrogen addition to polyynes leading also to radical-induced fragmentation that inhibits growth of polyynes to <20 carbon atoms in size. , An example of this could be hydrogen addition to a (Ai) – (Ai) crosslink providing the (Ai) – (E) crosslink leading to a significant decrease in bond energy.…”
Section: Resultsmentioning
confidence: 99%
“…This would require a full kinetic mechanism considering both the formation and fragmentation routes for both pathways. Both the aromatic and aliphatically bonded complexes have been shown to form bonds of sufficient energy to withstand flame temperatures, ,, however, both will be subject to radical-induced fragmentation to varying degrees. Examples of this are hydrogen abstraction from aliphatics leading to β-scission that leads to the rapid fragmentation of aliphatic fuels as well as hydrogen addition to polyynes leading also to radical-induced fragmentation that inhibits growth of polyynes to <20 carbon atoms in size. , An example of this could be hydrogen addition to a (Ai) – (Ai) crosslink providing the (Ai) – (E) crosslink leading to a significant decrease in bond energy.…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32] They added a chemical bond formation term that describes the formation of chemical bonds between PAHs and thus the scientific discussion currently shifts towards aliphatically bridged PAHs. 28,[33][34] These hypothesized compounds have only recently been identified in flame-sampling tandem mass spectrometry experiments. 35 In the same work, aliphatically substituted PAHs were identified, which might be of significance for particle inception as Violi and coworkers have shown that their dimers are more likely to survive elevated flame temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The particular reaction conditions in terms of molecular fuel structure, temperature, pressure, and other variables affect the internal nanostructure, chemical composition, mobility, and reactivity of soot particles [244] , [245] , [246] , [247] , [248] , [249] , which may be different in technical devices from laboratory reactors and flames. Attempts to link between PAHs, high-molecular-weight carbon structures, and initial particles has motivated theoretical work [199 , 250] as well as experimental approaches including in-situ LII [251] , [252] , [253] , probe-sampling tandem mass spectrometry (MS-MS) [254] , and ex-situ microscopy [207 , 252 , [255] , [256] , [257] , [258] to image carbon structures and particles while considering also probe sampling effects [259] .…”
Section: Selected Combustion Chemistry Advances – Overview and Recentmentioning
confidence: 99%